Uma origem multifractal para a turbulência no meio interestelar - Moraes Júnior, Pedro Ricardo Vasconcelos de (2017)
In recent years studies on complex systems have been gaining strength and tools to be able to simulate and verify their behavior statistically.Much of this is due to many systems that have come to behave in a nonlinear and dissipative way.For these cases conventional geometries such as Euclidean is not possible for the prowess of explaining it, with this the geometry of the fractals emerged as an important alternative for the treatment of this medium,being laws of scales (power) applying very well for this system being exemplified in the form of time series and surfaces (two-dimensional and three-dimensional geometries).Thus a variety of methods were counted for this treatment, among them are the analysis via exponent of Hurst and multifractal analysis.Our work aims to propose a new method to analyze two-dimensional images multifractally, being these images coming from clouds simulations of the interstellar medium.First step was to generate 12 MHD simulations in which they differed from values of pressure and magnetic field, then generated the 2D image that is applied on them the multifractal MFDMA treatment method.With the application of this method it is possible to evaluate the images through a frame containing the exponents of multifractal analysis, being possible to evaluate the scale behavior in the images and verify the degree of complexity, and to find out which sources cause multifractality,using two methods of multifractal analysis that are shuffling the original image data and replacing the original data from the Fourier transform.The results show that for all images the shuffling method can destroy the multifractal source of the original image and still behave like a monofractal,While the other method is ineffective, concluding that nonlinear factors are not included among the sources and indicating as a source of multifractality the long-range correlations. Other important results are the relation of degree of multifractity ∆h with pressure, sonic number of Mach and number of Alfvén.